Abemaciclib induces apoptosis in cardiomyocytes by activating the Hippo signaling pathway. (18th June 2020) - Zhou, Yajie; Li, Yanfei; Shen, Junwei; Li, Jue; Li, Xinming
Abstract: Abemaciclib is the newest cyclin-dependent kinase 4/6 inhibitor that has received approval from the US Food and Drug Administration for using in patients with advanced breast cancer. However, its potential adverse effects on cardiomyocytes remain unknown. In this study, we used the cell counting kit-8 assay, western blot analysis, flow cytometry, immunostaining, and quantitative polymerase chain reaction to investigate the role of abemaciclib in inducing apoptosis and in inhibiting the viability and proliferation of AC16 human cardiomyocyte cells. The results revealed that abemaciclib induced apoptosis and inhibited cell proliferation by activating the Hippo signaling pathway. This work demonstrates the molecular basis by which abemaciclib induces cardiac side effects, providing a theoretical basis and effective targets for the treatment of cardiac diseases.